Perancangan Intrusion Detection System Untuk Mendeteksi Serangan Menggunakan Aplikasi Telegram - Friska Yudhistira; Dahliyusmanto Dahliyusmanto; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Information technology is now much developed. With the ease of obtaining this information, it causes other obstacles, namely important information or data can be misused by other parties who are not responsible for their own benefit. So that a network security system becomes one of the important aspects to maintain the validity and integrity of data and ensure the availability of services for its users. The system should be equipped with security that allows it to be safe from all kinds of attacks and as well as intrusion attempts by irresponsible parties. With the IDS (Intrusion Detection System) administrator will detect the attack by an intruder so that notification of an attack can be identified quickly through a notification Telegram Sistem IDS (Intrusion Detection System)will provide notification or warning through application telegram if there are attacks on computer networks are detected in the system, so administrators networkable to find out the occurrence of the attack as soon as possible This system can detect attacks that occur on a computer network by scanning a number of sources and traffic that occurs within the network, so that all illegal events can be seen throughactivities monitoring using the application used to monitor the network, the IDS System. This will provide notifications or warnings via the Telegram application if an attack on the computer network is detected in the system, so that theadministrator networkcan find out the occurrence of the attack as quickly as possible.Of the 5 tests that have been carried out 80% successful 20% failed, it can be stated that the test was successfully carried out.Keywords: IDS (Intrusion Detection System), Snort, Telegram , Computer network.